Negotiation of Tradition and Modernity Practices and Meanings of Marriage Beliefs in the Mangir Community, Bantul - Sriyantini; Muhammad Iqbal Birsyada (Educia Journal, 2026)
This study examines the persistence and transformation of marriage beliefs within the Mangir community of Bantul Regency, Yogyakarta, Indonesia, in the context of increasing modernization and social change. While modernization is often associated with the decline of traditional practices, local marriage traditions in Mangir continue to influence decision-making and social behavior across generations. This research aims to explore how marriage beliefs are maintained, legitimized, and negotiated within contemporary social contexts. A qualitative case study approach was employed to investigate the experiences, interpretations, and practices of community members. Data were collected through in-depth interviews, participant observation, and document analysis involving traditional leaders, village officials, married community members, and younger-generation residents. The data were analyzed using the interactive model of qualitative analysis consisting of data condensation, data display, and conclusion drawing and verification. The findings reveal that marriage beliefs persist through the interaction of collective memory, personal experience, family socialization, and traditional authority. Practices such as petungan (auspicious day calculations), ngalang (ritual detouring), restrictions associated with Wednesday Pon, and post-marital residential norms function as culturally embedded mechanisms for managing uncertainty and preserving social harmony. The study further demonstrates that younger generations do not simply reject traditional beliefs but actively negotiate them through adaptive strategies that accommodate modern educational, occupational, and mobility demands while maintaining cultural legitimacy. These findings suggest that tradition and modernity are not mutually exclusive but coexist through continuous processes of cultural adaptation and reinterpretation. The study contributes to broader discussions on cultural resilience, community-based risk management, local wisdom, and the sustainability of traditional institutions in contemporary society.